Effects of Thoracic Paravertebral Block on Nociceptive Levels After Skin Incision During Video-Assisted Thoracoscopic Surgery - Miyawaki, Hiroki (Med Sci Monit, 2019)
BACKGROUND: Regional anesthesia provides excellent analgesic effects after surgery. However, the effects of regional anesthesia on nociceptive levels during surgery under general anesthesia have not been quantitatively evaluated. To reveal the effects of thoracic paravertebral block (PVB) on nociceptive levels after skin incision during general anesthesia, we performed a retrospective cohort study in patients without serious preoperative conditions or comorbidities undergoing elective video-assisted thoracoscopic surgery (VATS). Nociceptive levels during general anesthesia were calculated using our previously determined Nociceptive Response (NR) equation, which utilizes common hemodynamic parameters. MATERIAL/METHODS: Data on 77 adult patients who underwent VATS from May 2018 to August 2018 were retrospectively obtained from our institutional database. We then performed propensity score matching between patients who received thoracic PVB (PVB group: n=29) and those who did not (Control group: n=48). The averaged values of systolic blood pressure (SBP), heart rate (HR), perfusion index (PI), bispectral index (BIS), and NR from 10 to 5 minutes before skin incision (T0), 5 to 10 minutes (T1), 10 to 15 minutes (T2), 15 to 20 minutes (T3), and 20 to 25 minutes after skin incision (T4), were calculated. RESULTS: Twenty-four propensity score-matched patients in each group were analyzed. Mean NR values at T1 and T2 in the PVB group were significantly lower than those in the Control group. SBP, HR, PI, and BIS, however, showed no significant differences between the 2 groups, except for SBP at T2. CONCLUSIONS: Thoracic PVB prevented an increase in NR values, which quantitatively represent nociceptive levels under general anesthesia, in patients undergoing VATS.